State Failure and The Sunni-Shia Conflict in Sampang Madura - Siddiq, Akhmad; Imama, Lely Shofa; Febriansyah, Muhammad; Hisyam, Muhamad Ali (Pascasarjana IAIN Pontianak, 2023)
This paper attempts to explain the process of conflict reconciliation within the Sunni-Shia conflict in Sampang, Madura. The research tries to analyze the process and progress of the Sunni-Shia conflict through the discourse of state failure. It will not only figure out the discourse through political or security perspective, but also tries to view the failure and the weakness of the state from the conflict-transformation and social perspective. This research aims to look at how religious identity has been played within the process of conflict reconciliation and how the state failed to solve the Shia-Sunni conflict in Sampang. In doing so, the paper explains the history of Shia in Sampang Madura, the chronology of the conflict and its escalation, and the absence of the state within the long process of reconciliation.